Inovasi Pengemangan Cookies Berbasis Daun Kelor (Moringa Oleifera) Sebagai Asupan Nutrisi Ibu Hamil dalam Upaya Pencegahan Stunting pada Anak di Desa Kertawangi Kecamatan Cisarua Kabupaten Bandung Barat: Pengabdian - Azhari Arief Budiman; Shofia Rofiqotu Nadiya; Diah Ayu Dwi Nurmavita; Meyra Nurfathin Nadirah; Dhiya Nabila Hansa; Wadi’ah Oktaviana; Putri Zhafira Nurinalestari; Jaya Kusuma; Syahla Rhamadaniah; Ghibran Jihaadunnafsi; Miftahul Huda (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Stunting remains a serious challenge in health development in Indonesia, including in West Bandung Regency, which has a high prevalence. Stunting prevention efforts can be implemented during pregnancy through adequate and balanced nutrition. One local food with potential for utilization is Moringa oleifera leaves, known to contain high levels of protein, iron, vitamin A, vitamin C, calcium, and antioxidants. This study aims to explore public understanding, response, and acceptance of the innovation of developing moringa leaf-based cookies as additional nutritional intake for pregnant women in an effort to prevent stunting. The method used is descriptive qualitative with data collection techniques in the form of participatory observation, semi-structured interviews, and documentation. The activity was carried out on August 26, 2025, in Kertawangi Village, Cisarua District, West Bandung Regency, involving 10 participants consisting of PKK mothers, UPTKB mothers, pregnant women, and breastfeeding mothers. The results of the activity showed that participants were enthusiastic, understood the benefits of moringa leaves, and were able to practice making moringa leaf cookies independently. Cookies are considered a healthy, easy-to-make snack with the potential to be developed into a highly nutritious local food alternative to support stunting prevention. Furthermore, this innovation also opens up opportunities for family economic empowerment through the use of moringa leaves as a functional food ingredient.